1985
DOI: 10.2307/3676630
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Biology of the Svalbard Rock Ptarmigan Lagopus mutus hyperboreus

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 5 publications
4
69
1
Order By: Relevance
“…As observed in other populations of rock ptarmigan (MacDonald, 1970;Weeden and Theberge, 1972;Olpinski, 1986), initiation of laying of first nests was highly synchronous at Windy Lake, both within and between years and between adult and yearling hens. However, initiation of laying was not correlated with body weight before incubation, as Steen and Unander (1985) found in Svalbard. Steen and Unander (1985) also found that yearling rock ptarmigan hens, which weighed significantly less than adults, initiated egg-laying later than adult hens; they surmised that the later initiation by yearlings was more a function of the condition of the hen, as expressed in body mass, than of age and breeding experience.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…As observed in other populations of rock ptarmigan (MacDonald, 1970;Weeden and Theberge, 1972;Olpinski, 1986), initiation of laying of first nests was highly synchronous at Windy Lake, both within and between years and between adult and yearling hens. However, initiation of laying was not correlated with body weight before incubation, as Steen and Unander (1985) found in Svalbard. Steen and Unander (1985) also found that yearling rock ptarmigan hens, which weighed significantly less than adults, initiated egg-laying later than adult hens; they surmised that the later initiation by yearlings was more a function of the condition of the hen, as expressed in body mass, than of age and breeding experience.…”
Section: Discussionmentioning
confidence: 58%
“…However, initiation of laying was not correlated with body weight before incubation, as Steen and Unander (1985) found in Svalbard. Steen and Unander (1985) also found that yearling rock ptarmigan hens, which weighed significantly less than adults, initiated egg-laying later than adult hens; they surmised that the later initiation by yearlings was more a function of the condition of the hen, as expressed in body mass, than of age and breeding experience. A similar relationship was observed for willow ptarmigan from northwestern British Columbia, where Hannon et al (1988) noted that hens which laid early were significantly heavier that those that laid in middle or later periods.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Since sea bird cliffs with lush vegetation and potential winter forage for ptarmigan are widely scattered along the whole coastline of Svalbard, one should not expect any uniform migration pattern (i.e. direction and So far, we must rely on observations of the sex-segregated flocks returning to the breeding areas reported by Steen and Unander (1985), where males arrived to the same territories in late March while hens arrived to the same breeding areas in early April. During autumn, the Svalbard rock ptarmigan gather in groups foraging under sea bird cliffs or other areas with rich vegetation for a few weeks before they leave the area (Løvenskiold 1964, Unander and.…”
Section: Satellite Tag Performancementioning
confidence: 99%
“…Although no quantitative information is available, observation indicates that Svalbard rock ptarmigan use separate habitats during the winter-and the breeding season. Steen and Unander (1985) observed flocks of ptarmigan returning to the breeding grounds in early spring, cocks arrived first in mid-March followed by hens in early April. Shortly after arrival, the cocks establish territories and the pairs stay on the territories until after hatching of the broods .…”
mentioning
confidence: 99%